Typology of rural areas in the Central and Eastern European EU new member States - Sabine Baum; Christian Trapp; Peter Weingarten (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2004)
Rural areas in Central and Eastern Europe are very often associated with a backwardness in terms of income and employment opportunities, a high dependency on agriculture, the outmigration of young, skilled people, a low population density and an insufficient infrastructure. In this paper 3 typologies are presented, which show that rural areas cannot be considered homogeneous and not all of them need the same developmental measures. The first typology classified all NUTS-3 regions in the ten Central and Eastern European countries (CEEC-10) by means of cluster analysis according to 7 demographic and socio-economic criteria. The result revealed 5 different types of regions as most adequate: three are largely rural, one includes both rural, and especially industrialised urban areas, and one covers only large cities. Narrowing the geographical focus to a single country in general improves data availability and allows to include more variables. In our case, Bulgaria, 16 variables on the NUTS-3 level could be condensed by factor analysis to 3 factors, which can be considered as structuring forces in rural Bulgaria: agglomeration, marginality and employment. Based on these factors, 6 groups of rural regions could be identified. The third analysis widened the geographical focus and included beside the NUTS-2 regions of the CEEC-10 also whose of the EU-15 (without UK). The first results of this cluster analysis with 12 variables revealed large developmental differences between these 2 country groups. The 3 typologies presented for different geographical areas provide no code of practice for regional policy measures, but important first clues for the elaboration of adapted rural development measures in CEE. – – Ländliche Räume in Mittel- und Osteuropa (MOE) werden häufig assoziiert mit ökonomischer Rückständigkeit, schlechten Beschäftigungsmöglichkeiten, einer hohen Abhängigkeit von der Landwirtschaft, der Abwanderung junger, ausgebildeter Arbeitskräfte, einer geringen Bevölkerungsdichte und einer unzureichenden Infrastruktur. In diesem Beitrag werden drei Typisierungen vorgestellt, die zeigen, dass ländliche Räume nicht als homogen betrachtet werden können und deshalb auch nicht alle dieselben Entwicklungsmaßnahmen benötigen. Die erste Typisierung mithilfe einer Clusteranalyse klassifizierte die NUTS-3-Regionen der 10 mittel- und osteuropäischen Länder (MOEL-10) auf der Basis von sieben demographischen und sozio-ökonomischen Variablen. Sie führte zu fünf Raumtypen: drei davon sind weithin ländlich geprägt, einer umfasst sowohl ländliche und als auch städtisch-industrielle Gebiete und der letzte Raumtyp repräsentiert die großen Städte. In einer zweiten Analyse wurde mit Bulgarien ein einzelnes Land auf NUTS-3-Ebene betrachtet, was in der Regel die Datenverfügbarkeit verbessert und es erlaubt, mehr Variablen in die Analyse mit einzubeziehen. Die berücksichtigten 16 Variablen konnten mithilfe der Faktoranalyse auf drei Faktoren zurückgeführt werden, welche die räumliche Struktur des ländlichen Bulgariens erklären: Agglomeration, Marginalisierung und Beschäftigung. Anhand dieser Faktoren konnten sechs Typen von ländlichen Räumen identifiziert werden. Die dritte Analyse erweitert den geographischen Blickwinkel und umfasst neben den NUTS-2-Regionen der MOEL-10 auch jene der EU-15 (ohne das VK). Hierbei werden große Entwicklungsunterschiede zwischen beiden Ländergruppen deutlich. Die drei Typisierungen bieten in der vorliegenden Form keinen Leitfaden für regionalpolitische Maßnahmen, jedoch wichtige erste Hinweise für die Erarbeitung angepasster ländlicher Entwicklungsprogramme in Mittel- und Osteuropa.
urn:nbn:de:gbv:3:2-22546
Keywords: C19; P25; R12; 330; Rural area; typology; Central and Eastern Europe; cluster analysis; Ländlicher Raum; Typisierung; Mittel- und Osteuropa; Clusteranalyse